Tumor rejection antigen gp96/grp94 is an ATPase: implications for protein folding and antigen presentation. - Li, Z (1993)
Immunization of mice with gp96/grp94 heat shock proteins (HSPs) elicits tumor-specific cellular immunity to the tumors from which gp96 is isolated. However, the cDNA sequence of gp96 is identical among tumors and normal tissues. This raises the question regarding the structural basis of the specific immunogenicity of gp96. As HSPs bind a wide array of molecules including peptides, we have proposed that gp96 may not be immunogenic per se, but may chaperone antigenic peptides. Furthermore, gp96 is localized predominantly in the lumen of the endoplasmic reticulum (ER) suggesting that it may act as a peptide acceptor and as accessory to peptide loading of MHC class I molecules. We demonstrate here that gp96 molecules contain ATP-binding cassettes, bind ATP and possess an Mg(2+)-dependent ATPase activity. Gp96 preparations are also observed to contain tightly bound peptides, which can be eluted by acid extraction. These properties of gp96 are consistent with its proposed roles in chaperoning antigenic peptides and in facilitating MHC class I--peptide assembly in the ER lumen. We present a model to explain how interaction of gp96 with MHC class I may result in transfer of peptides to the latter.